Addressing gaps in international blood availability and transfusion safety in low‐ and middle‐income countries: a NHLBI workshop. Issue 5 (14th March 2018) - Custer, Brian; Zou, Shimian; Glynn, Simone A.; Makani, Julie; Tayou Tagny, Claude; El Ekiaby, Magdy; Sabino, Ester C.; Choudhury, Nabajyoti; Teo, Diana; Nelson, Kenrad; Peprah, Emmanuel; Price, LeShawndra; et al.
Abstract : In April 2017, a workshop sponsored by the National Heart, Lung, and Blood Institute, Division of Blood Diseases and Resources, and the Center for Translation Research and Implementation Science was held to discuss blood availability and transfusion safety in low‐ and middle‐income countries (LMICs). The purpose of the workshop was to identify research opportunities for implementation science (IS) to improve the availability of safe blood and blood components and transfusion practices in LMICs. IS describes the late stages of the translational research spectrum and studies optimal and sustainable strategies to deliver proven‐effective interventions. Regional working groups were formed to focus on opportunities and challenges in East Africa, Central/West Africa, Middle East and North Africa, Latin America and the Caribbean, Southeast Asia, Western Pacific Asia, Eastern Europe, and Central Asia. The need for an "adequate supply of safe blood" emerged as the major overriding theme. Among the regional working groups, common cross‐cutting themes were evident. The majority of research questions, priorities, and strategies fell into the categories of blood availability, blood transfusion safety, appropriate use of blood, quality systems, health economics and budgeting, and training and education in IS. The workshop also brought into focus inadequate country‐level data that can be used as the basis for IS initiatives. A mixed approach of needs assessment and targeted interventions with sufficient evidence base to move toward sustainment is an appropriate next step for blood availability and transfusion safety research in LMICs.